Answer:
To find the equation of the line that passes through the points (2,3) and (-5,6), we can use the point-slope form of a linear equation, which is given by:
y - y1 = m(x - x1)
where (x1, y1) is one of the given points on the line, and m is the slope of the line.
First, let's find the slope of the line using the two given points:
m = (y2 - y1) / (x2 - x1)
= (6 - 3) / (-5 - 2)
= 3 / (-7)
= -3/7
Now we can choose either of the given points and substitute it for (x1, y1) in the point-slope form. Let's use (2,3):
y - 3 = (-3/7)(x - 2)
Simplifying the right-hand side, we get:
y - 3 = (-3/7)x + (6/7)
Adding 3 to both sides, we get:
y = (-3/7)x + (27/7)
Therefore, the equation of the line that passes through the points (2,3) and (-5,6) is y = (-3/7)x + (27/7).
Explanation: